Na putiakh perestroiki . Na putiakh perestroiki . Perestroika Ways . На путях перестройки - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Three documentaries about the progress of perestroika, revealing the policy mistakes of the Soviet leadership before and after the start of perestroika. Film 1 exposes the Stalin cult. Contributors: Gabrilovich, Aleksei (Director) Трехсерийный фильм о ходе перестройки раскрывает ошибки в политике советских лидеров. Фильм первый рассказывает о культе Сталина. Создатели: Габрилович, Алексей (Режиссер)